1979
DOI: 10.1093/nar/6.11.3673
|View full text |Cite
|
Sign up to set email alerts
|

Release of 7-methylguanine residues whose imidazole rings have been opened from damaged DNA by a DNA glycosylase from Escherichla coli

Abstract: Double-stranded DNA containing 7-methylguanine residues whose imidazole rings have been opened, i.e. 2,6-diamino-4-hydroxy-5-N-methylformamido-pyrimidine residues, may be prepared by treatment of DNA with dimethyl sulfate followed by prolonged incubation at pH 11.4. These substituted formamidopyrimidine residues are actively removed from DNA by a DNA glycosylase present in E. coli cell extracts. The enz;me shows no apparent cofactor requirement and has a molecular weight of about 30 000. The release of ring-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
153
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(162 citation statements)
references
References 15 publications
8
153
0
1
Order By: Relevance
“…In a recent study (5), the transformation of primary breast tumors to the metastatic state was shown to involve a Ͼ2-fold increase in ⅐OH damage in DNA, as indicated by modified nucleotide base models comprising mutagenic 8-hydroxyadenine (6) and the putatively nonmutagenic ring-opened product 4,6-diamino-5-formamidopyrimidine (fapyadenine; refs. [7][8][9][10][11]. In addition, plots of the modified nucleotide base model log 10 (fapyadenine͞8-hydroxyadenine) versus the size of metastatic and nonmetastatic breast tumors revealed that the metastatic tumor DNA had significantly greater structural diversity than the nonmetastatic tumor DNA (P ϭ 0.01; ref.…”
mentioning
confidence: 99%
“…In a recent study (5), the transformation of primary breast tumors to the metastatic state was shown to involve a Ͼ2-fold increase in ⅐OH damage in DNA, as indicated by modified nucleotide base models comprising mutagenic 8-hydroxyadenine (6) and the putatively nonmutagenic ring-opened product 4,6-diamino-5-formamidopyrimidine (fapyadenine; refs. [7][8][9][10][11]. In addition, plots of the modified nucleotide base model log 10 (fapyadenine͞8-hydroxyadenine) versus the size of metastatic and nonmetastatic breast tumors revealed that the metastatic tumor DNA had significantly greater structural diversity than the nonmetastatic tumor DNA (P ϭ 0.01; ref.…”
mentioning
confidence: 99%
“…Ames (1983) has drawn attention to the large number of environmental mutagens, including substances in food, which might act through the formation of oxygen radicals. Several repair enzymes that act on DNA exposed to oxidising agents have been characterised in our laboratory: these include (i) formamidopyrimidine-DNA glycosylase, which catalyses the release of potentially cytotoxic purine residues with an opened imidazole ring from y-ray-irradiated DNA (Chetsanga & Lindahl, 1979;Boiteux & Laval, 1983;Breimer, 1984); (ii) a separate DNA glycosylase which releases urea (a remnant of thymine) and several other derivatives with fragmented pyrimidine rings from oxidised DNA (Breimer & Lindahl, 1980 -this enzyme is identical with endonuclease III, which removes thymine glycol from DNA (Demple & Linn, 1980); (iii) a Mg2 + independent endonuclease for apurinic sites in DNA, endonuclease IV (Ljungquist et al, 1976;Ljungquist, 1977;Demple et al, 1986), which also removes 3-phosphoglycolate residues from 3' termini of damaged DNA. Two distinct DNA glycosylases with the specificities described are found both in E. coli and in human cells (Breimer, 1983(Breimer, , 1984.…”
Section: T Lindahlmentioning
confidence: 99%
“…It is known that the glycosylases can have multiple specificities. Bacterial FPG was first shown to act on ring-opened purines [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the glycosylases can have multiple specificities. Bacterial FPG was first shown to act on ring-opened purines [4].To test the specificities of the plant enzymes, we have inserted cDNAs for OGG and FPG from Arabidopsis thaliana into Escherichia coli strains, devised by Cupples and Miller [5] to test for single-base substitution mutations, in which the endogenous FPG gene has been inactivated [6]. There are six Cupples and Miller [5] strains, each with a base-pair substitution in its LacZ gene that inactivates the product b-galactosidase.…”
mentioning
confidence: 99%